THE DEVELOPMENT OF THE MEAT MARKET IS AN INTEGRAL BUILDING A LOGISTICS SYSTEM AT THE BUSINESS ORGANIZATION LEVEL - Kokenova A.T.; Syzdykov B.Sh.; Balabekova D.D.; Sabenova B.N.; Abylkasym A.B. (Academic Journal of Physical and Chemical Sciences, 2020)
The stability and financial well-being of an enterprise is ensured by its business activity and behavior in a particular market segment. In a competitive environment, it is necessary to constantly monitor the appearance of new, cheaper and sufficiently effective developments, adapt to changes in the market situation in a timely manner, and accordingly review the existing principles of the company's functioning. Well-established concepts, ways of organizing and conducting business that were acceptable and acceptable to the company's management yesterday can negatively affect the dynamics of the company's development today. To not only achieve, but also maintain the position of a leader, the company needs to increase the level of technology and efficiency of business processes. Success in attracting potential customers depends on the efficiency and clarity of the customer's requirements. Failure to comply with at least one of the requirements may result in the loss of consumers and the corresponding market share. In a competitive environment, customers have the opportunity to compare and choose the best level of service and, accordingly, make higher demands on its quality. The quality of logistics services is the satisfaction of customers' requests, expressed in the proper execution of orders, the absence of errors, effective provision of services, as well as a constant desire to improve the level of service. The article considers the specifics of building a logistics strategy at an industrial enterprise, analyzes and describes the algorithm for building a first-level logistics system. It is determined that the General strategy of an industrial enterprise as a whole plays an important role in the construction of a logistics strategy. The organizational structure of the logistics service of an industrial enterprise is considered and studied, the purpose of which is to provide system management of commodity flows of the enterprise. Special attention is paid to the subsystems of macro and micrologistic systems, infrastructure aspects of their development taking into account the factors of the global economy. The focus of logistics systems on the macroeconomic effect is determined by their perspective role in the development of the economy of the Republic of Kazakhstan, which affects the innovative aspects of the development of industry and business processes. In the future, logistics systems can be widely developed and spread not only in terms of material flows, but also in terms of the information component, the dynamics of the movement of HR resources, which will optimally integrate the economy of Kazakhstan into global and cross-border production and economic systems. As a result, new economic theories can be developed for building and designing logistics for foreign economic unions, interaction between customs authorities, and improving the principles and methodology of competition in international markets for goods and services. The theoretical research carried out is of an applied nature and can be widely distributed.